2023
DOI: 10.1111/ahg.12501
|View full text |Cite
|
Sign up to set email alerts
|

A novel nonsense variant in the ATL3 gene is associated with disturbed pain sensitivity, numbness of distal limbs and muscle weakness

Abstract: IntroductionHereditary sensory neuropathy (HSN) describes as a heterogeneous group of peripheral neuropathies. HSN type 1 (HSN1) is one subtype characterized by distal sensory impairment that occurs in the form of numbness, tingling, or pain. To date, only two variants in the atlastin GTPase 3 (ATL3) gene have been identified that result in hereditary sensory neuropathy type 1F (HSN1F) with autosomal dominantinheritance. MethodsWe sudied and examined who present with sensory disturbances and muscle weakness in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 31 publications
(39 reference statements)
1
2
0
Order By: Relevance
“…NGS analysis did not reveal any other possible pathogenic variation that could explain the patient's symptoms. patient presented in this study developed typical HSN1F clinical symptoms, such as sensory troubles limited to lower limbs, paresthesia, and altered tendon reflexes, which could be compatible with a variation in ATL3, such as those described in previous studies presenting point mutations in ATL3 [5,[12][13][14][15].…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…NGS analysis did not reveal any other possible pathogenic variation that could explain the patient's symptoms. patient presented in this study developed typical HSN1F clinical symptoms, such as sensory troubles limited to lower limbs, paresthesia, and altered tendon reflexes, which could be compatible with a variation in ATL3, such as those described in previous studies presenting point mutations in ATL3 [5,[12][13][14][15].…”
Section: Discussionsupporting
confidence: 78%
“…Moreover, for both Bosnian and Chinese families, patients’ electrophysiologic studies showed decreased amplitude of sensory nerves and slightly reduced sensory nerve conduction velocities, suggesting an axonal degeneration of the distal sensory nerves [ 12 , 13 ]. Recently, a novel nonsense variant (c.16C > T, p.Arg6*) in ATL3 has been described in two Iranian families presented with distal impairment of sensory function disturbing superficial touch in the soles and absence of any neuropathic symptom in the upper limbs [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…We also have observed a shift in editing targets, where the same gene is being edited in control and infection, but at a different position. For instance, the Atl3 gene associated with cellular integrity and cytokinesis (Mohammadi et al, 2023) has only one edited site in 3’UTR at positions 7538115 and 7535531 in control and muReoV respectively. One explanation for that phenomenon could be that RNA editing is condition-specific (Liew et al, 2017), and/or reflect the effect of other unknown factors that regulate host-virus interactions (Piontkivska et al, 2021).…”
Section: Tablementioning
confidence: 99%